(untitled) (Global Journal of Human-Social Science, 2021)
Several commerical quantum computers are now available that offer Hybrid Classical-Quantum computing Application is made to a classical-quantum model of human neocortex Statistical Mechanics of Neocortical Interactions SMNI which has had its applications published in many papers since 1981 However this project only uses Classical super- computers Since 2015 PATHINT has been used as a numerical algorithm for folding path-integrals Applications in several systems in several disciplines has generalized been from 1 dimension to N dimensions and from classical to quantum systems qPATHINT Papers have applied qPATHINT to neocortical interactions and financial options The classical space described by SMNI applies nonlinear nonequilibrium multivariate statistical mechanics to synaptic neuronal interactions while the quantum space described by qPATHINT applies synaptic contributions from Ca2 waves generated by astrocytes at tripartite neuron-astrocyte-neuron sites